Coalition governments and electoral alliances: Patterns in indian parliamentary politics (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The formation of coalitions and alliances of electoral parties has become a hallmark of the Indian parliamentary politics as the nation in the country shifts towards having a multi-party rather than a dominant-party system. The paper will discuss the trends, development, and operation of coalition politics in India and how it was based on federalism, social diversity, and electoral necessities. It uses a historical approach to the formation of coalitions, with one-party rule, to the acceptance of alliances, and to the formation of dominant parties' coherent coalitions in the last years. The paper also compares various kinds of electoral alliances- pre- poll, post-poll, and issue-based and their strategic importance in influencing electoral outcomes in the first-past-the- post system. Additionally, the paper examines the institutional designs that perpetuate coalition governance, such as power-sharing arrangements, Common Minimum Programmes, and coordination structures. It detects some important trends of fragmentation of party systems, the emergence of regional parties, and pragmatic, as well as ideological, alliances. Although coalition politics promotes inclusiveness and robust representation of the federal government, it faces issues to deal with in terms of stability, policy coherence, and decision-making effectiveness. The paper arrives at a conclusion that coalition politics is one of the structural and developing characteristics of Indian democracy, and that governance should be a stable institution that must be guided by good leadership and innovation of the institutions.